The role of misinformation effect on memory recall. - Anciro, Catherine N. (2005)
Memory is critical to humans and all other living organisms. It allows us to retrieve events from the distant past or from moments ago. The exposure to distorted memories in misleading information from others could somehow affect our memory traces without being aware of it. With this, the researchers aimed to provide evidences of the role of misinformation effect in memory recall. The group viewing sessions was utilized in the study. The participants were randomly selected from the third year BS Criminology students of DLSU-D considering the demographic selection criteria and with the use of researcher-made questionnaires. Findings of the study revealed that misleading information has no effect in our memory recall and the data gathered illustrated that there is no significant difference between the memory scores of the control and experimental group before and after the treatment.